Legal Consequences of Violating The Halal Certification Process Through A Self-Declaration Scheme - Vinka Ananda Putri; Muthia Sakti (Journal of Law, Politic and Humanities, 2024)
All micro and small enterprises must register their products under the Halal Product Guarantee Organising Agency's (BPJPH) halal certification program in order to obtain halal certification. BPJPH streamlines the process by offering a more straightforward method for halal certification registration, which involves utilizing the self-declaration scheme. However, this certainly does not excuse violations committed by business actors or other parties. Therefore, the purpose of this research is to shed light on BPJPH's monitoring role in the halal certification process via the self-declare scheme, and to outline the legal repercussions for those who violate these stages. We conducted the research using a normative juridical approach, collecting primary data from statutory regulations and supplementing it with interviews. The research findings show that BPJPH carries out a supervisory function over the halal certification process through a self-declare scheme. This research also reveals that the self-declare scheme will impose administrative sanctions on violators at the halal certification stages. However, the imposition of administrative fines is not yet feasible. We are still studying the limits of fines and the types of violations committed.